Historical analysis of the records of sylvan yellow fever in the State of Amazonas, Brazil, from 1996 to 2009 - Maria das Graças Gomes Saraiva; Raul Diniz Souza Amorim; Marco Antônio Sabóia Moura; Eyde Cristianne Saraiva dos Santos; Leônidas Sales Sampaio; Maria das Graças Vale Barbosa; Samira Bührer-Sékula (Revista da Sociedade Brasileira de Medicina Tropical, 2013)
Introduction Yellow fever is a non-contagious infectious disease, highly lethal, transmitted by the Aedes, Haemagogus and Sabethes. Methods Descriptive retrospective study of the yellow fever cases in Amazonas, between 1996 and 2009. Results Forty two cases of yellow fever were confirmed, with 30 deaths, 10% of which were foreigners. Conclusions The presence of Aedes aegypti and Aedes albopictus in both rural Amazonas and its capital demonstrates the dispersion of these vectors and underscores the need for better and continuous epidemiological and entomological control.